Characterization and degradation state of the trails in Caparaó National Park - Almeida, Marcello Pinto de; Lima, Gumercindo Souza; Martins, Sebastião Venâncio; Bontempo, Gínia César (Floresta, 2019)
A large increase in visitation has recently been observed in Brazilian protected areas. The presence of visitors can cause changes in the environment, generating certain unwanted impacts. Therefore, the objective of this study is to assess the visitation at Caparaó National Park, map the main trails open to the public, and determine their degree of degradation. To define the most relevant trails for this study, the following criteria were used: visitation demand, impact intensity, and zoning. The elevation profile and other physical attributes of the selected trails were obtained by GPS. Erosion was established as the predominant impact, and the length of eroded stretches on each trail was evaluated. The trail to Pico da Bandeira through Casa Queimada has a greater declivity, and, although it sees fewer visitors than the trail to Pico da Bandeira through Tronqueira, it shows a higher erosion rate. This result indicates that, in certain cases, the declivity can contribute more significantly to the increase in erosion than the number of visitors.